Rotationally asymmetrical compound parabolic concentrator for concentrating photovoltaic applications - Abu-Bakar, S.H.; Muhammad-Sukki, F.; Ramirez-Iniguez, R.; Mallick, T.K.; Munir, A.B.; Yasin, S.H.M.; Rahim, R.A. (Elsevier, 2014)
This paper describes a novel type of solar concentrator - a rotationally asymmetrical compound parabolic concentrator (RACPC). The RACPC aims at addressing the following objectives: (i) to increase the electrical output of a concentrating photovoltaic (CPV) system by providing sufficient concentration gain; (ii) to minimise the usage of the PV material with the corresponding reduction of CPV system cost, and (iii) to eliminate the requirement of mechanical tracking by providing a wide field-of-view. This paper first provides a short review on variations of compound parabolic concentrator designs available to date. Next, the process of designing the RACPC is presented and the geometrical concentration gain of the concentrator is discussed. In addition, the optical concentration gain is also presented for various angles of incidence. Through simulations, it is demonstrated that the RACPC can provide significant optical concentration gains within its designed acceptance angle. An RACPC based system is an attractive alternative to conventional solar photovoltaic systems. (C) 2014 Elsevier Ltd. All rights reserved.